Animal farm : a fairy story - Orwell, George, e uthor (Richmond, United Kingdom : Alma Classics, 2023)
A satirical allegory set on a farm where animals overthrow their human owner, only to see their own society corrupted by tyranny and inequality.
Originally published in 1945.
In English.
Keywords: Totalitarianism -- Fiction; Political satire, English; Domestic animals -- Fiction; Farm life -- Fiction